The mediating effect of Islamic ethical identity disclosure on financial performance - Mutmainah, Ina; Apriliantika, Annisa (Asian Journal of Islamic Management (AJIM), 2023)
Purpose – The present study examines the impact of Islamic corporate governance and social responsibility on financial performance.Methodology – The study was designed with a quantitative approach. Purposive sampling was used in this study. Data were garnered through panel data from annual reports on Islamic banking in Indonesia and Malaysia from 2018 to 2020. The data were analyzed employing the Path Analysis.Findings – Study findings demonstrate that Islamic social responsibility and corporate governance did not significantly impact financial performance. Additionally, disclosing its Islamic ethical identity, Islamic corporate governance had a substantial impact on financial performance. Islamic social responsibility, however, had no impact on financial performance when Islamic ethical identity was disclosed.Implication – The findings offer empirical insights for managing Islamic commercial banks in Indonesia and Malaysia to elevate the application of Islamic corporate governance and social responsibility. This transparently demonstrates the quality of governance and social responsibility of Islamic banking with the disclosure of Islamic ethical identity following the standards applied by Islamic banking affecting stakeholder satisfaction.Originality – This research contributes significantly to the realm of Islamic banking management. It examines the level of stakeholder satisfaction through the enactment of Islamic corporate governance as a form of supervision of management performance, Islamic social responsibility as a form of corporate concern for the surrounding environment and Islamic ethical identity disclosure to promote the image of Islamic banking.